A Comparative Study of Nanofibers from Regenerated Cotton and Jute. Issue 1 (31st December 2023) - Anjuman Ara, Zinia; Wang, Lijing; Padhye, Rajiv; Wang, Xin
ABSTRACT: Nanofibers electrospun from cellulose sources have received substantial attention. Using trifluoro acetic acid (TFA) as the solvent, dissolved cotton and jute were comparatively electrospun to cotton nanofibers (CNFs) and jute nanofibers (JNFs), respectively. The viscosity and conductivity of the as-prepared polymer solutions were measured. The morphology, chemical structure, thermal stability and decomposition pattern together with the crystallinity index of the JNFs and CNFs were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) analysis, thermogravimetric analysis (TGA) and X-ray diffraction (XRD), respectively. SEM analysis showed no major differences in surface morphology between JNFs and CNFs. The TGA results confirmed that the as-spun nanofibers have excellent thermal stability up to 210 ºC temperature before cellulose decomposition. The JNFs showed a similar degradation pattern as the CNFs. The results of this work will contribute to proposing appropriate applications of electrospun nanofibers from jute.